6.5k views
4 votes
Taylor graphs the system below on her graphing calculator and decides that f(x)=g(x) at x=0, x=1, and x=3. Provide Taylor with some feedback that explains which part of her answer is incorrect and why it is incorrect.

f(x)= 2x+1
g(x)= 2x^2+1

User Kc Bickey
by
6.8k points

1 Answer

2 votes

Answer:

At x = 3 . It is incorrect

f(x) ! = g(x)

Explanation:

Lets evaluate each case

x = 0

f(0) = 2*(0) +1 = 0 + 1 = 1

g(0) = 2*(0)^2 +1 = 0 + 1 = 1

Then f(0) = g(0) = 1


x = 1

f(1) = 2*(1) +1 = 2 + 1 = 3

g(1) = 2*(1)^2 +1 = 2 + 1 = 3

Then f(1) = g(1) = 3


x = 3

f(3) = 2*(3) +1 = 6 + 1 = 7

g(3) = 2*(3)^2 +1 = 18 + 1 = 19

Then f(3) != g(3) (They are different)

User Benface
by
6.2k points